First annual register of allergenic pollen in Talca, Chile (2013)
ABSTRACT: Background There are no data on atmospheric pollen in Talca. In the present work, our aim is to describe the amount of pollen grain in the atmosphere of the city of Talca likely to cause pollinosis of its inhabitants. Methods A volumetric Hirst sampler (Burkard seven-day recording device) was used to study pollen levels. It was placed in the centre of Talca from May 2007 to April 2008. Results The highest airborne presence of pollen, as measured in weekly averages, was Platanus acerifolia with a maximum weekly daily average of 203grains/m3 registered during September and October. The second highest was Acer pseudoplatanus with a maximum weekly daily average of 116grains/m3. Populus spp. had a maximum weekly daily average 103grains/m3. Olea europaea reached 19grains/m3 in November. Grasses presented high levels of pollen counts with a maximum weekly daily average of 27grains/m3 from the end of August until the end of January. Pollens of Plantago spp. Rumex acetosella and Chenopodium spp. had a similar distribution and were present from October to April with maximum weekly daily average of 7grains/m3, 7grains/m3 and 3grains/m3 respectively. Significant concentrations of Ambrosia artemisiifolia were detected from February until April. Conclusion The population of Talca was exposed to high concentrations of allergenic pollen, such as P. acerifolia, A. pseudoplatanus, and grasses in the months of August through November. The detection of O. europaea and A. artemisiifolia is important as these are emergent pollens in the city of Talca. Aerobiological monitoring will provide the community with reliable information about the level of allergenic pollens, improving treatment and quality of life of patients with respiratory allergy.